Mind the gap: household's knowledge and action in energy efficiency behaviour - Zainudin, Norzalina; Nordin, Nurnaddia; Nordin, Nurhaiza (Faculty of Business, Economics and Accountancy, Universiti Malaysia Sabah, 2017)
This objective of paper is to identify the relationship between environmental knowledge and action among Malaysian households. This body of work therefore aims to develop a perspective theoretically grounded in a more dialectical understanding of the relations between household’s knowledge and action toward buying energy efficient products in Malaysian market. A cluster sampling method was employed. A total of 500 face to face interviewed questionnaires were distributed in the shopping area and electrical shops in two regions in Peninsular Malaysia. In total, 392 usable Malaysian consumer responses were collected and used for analysis. The reliability test on all these constructs produce satisfactory reliability coefficient. Results of structural equation model indicate that there are significant relationships among these constructs. The result shows perceived advantages of products, subjective norm and responsibility are significantly related through the mediating effect of attitude. It is hoped that the findings and discussion will contribute to the theory of consumer behaviour, as well as to offer insightful knowledge for practical consideration.